Retrospective analysis of the incidence and outcome of late acute and chronic graft-versus-host disease—an analysis from transplant centers across Europe - Langer, Ronja; Lelas, Antonela; Rittenschober, Michael; Piekarska, Agnieszka; Sadowska-Klasa, Alicja; Sabol, Ivan; Desnica, Lana; Greinix, Hildegard; Dickinson, Anne; Inngjerdingen, Marit; Lawitschka, Anita; Vrhovac, Radovan; et al. (Frontiers in Transplantation, 2024)
Chronic graft-versus-host disease (cGvHD) is a serious late complication of allogeneic hematopoietic stem cell transplantation (allo-HSCT). This multicenter analysis determined the cumulative incidence (CI) of cGvHD and late acute GvHD (laGvHD) and its impact on transplantation-related mortality (TRM), relapse (R), and overall survival (OS) in 317 patients (296 adults, 21 pediatrics [<12 years of age]) who underwent their first allo-HSCT in 2017. The CI of laGvHD was 10.5% in adults and 4.8% in pediatrics, and the CI of cGvHD was 43.0% in all adult transplant patients and 50.2% in the adult at-risk cohort at the study end. The onset of cGvHD was de novo in 42.0% of patients, quiescent in 52.1%, and progressive in 5.9%. In adults, prophylactic use of antithymocyte globulin or posttransplant cyclophosphamide was associated with a significantly lower incidence of cGvHD (28.7%) versus standard prophylaxis with calcineurin inhibitors (30.6%) and methotrexate/mycophenolate mofetil (58.4%) (all p<0.01). TRM was significantly higher in patients with aGvHD (31.8%) versus cGvHD (12.6%) and no GvHD (6.3%) (all p=0.0001). OS in the adult at-risk cohort was significantly higher in patients with cGvHD (78.9%) versus without (66.2%; p=0.0022; HR 0.48) due to a significantly lower relapse rate (cGvHD: 14.5%; without cGvHD: 27.2%; p=0.00016, HR 0.41). OS was also significantly higher in patients with mild (80.0%) and moderate (79.2%) cGvHD versus without cGvHD (66.2%), excluding severe cGvHD (72.7%) (all p=0.0214). The negative impact of severe cGvHD on OS suggests a focus on prevention of severe forms is warranted to improve survival and quality of life.